8.CURRENT SITUATION OF ANXIETY DISORDERS IN 10th GRADE STUDENTS IN THE CHOICE OF SUBJECT COMBINATION UNDER THE 2018 GENERAL EDUCATION PROGRAM IN HO CHI MINH CITY PERIOD FROM 2022-2024 AND RELATED FACTORS (Vietnam Journal of Community Medicine, 2025)
Objective: Identify the rate of anxiety disorders and related factors in 10th grade students in choosing subject combinations according to the 2018 educational program in Ho Chi Minh city from 2022-2024.Method: Cross-sectional descriptive study on 1288 students, the assessment tool is the zung scale.Results: The rate of anxiety disorders in students is 17.3%, among them, anxiety disorders are mild (14.9%), moderate (2%), severe (0.2%), very severe (0.2%). Factors related to anxiety disorders in research subjects: 10th grade students in the 2022-2023 school year have 2.17 times more anxiety disorders compared to the 2024-2025 school year and 10th grade students in the 2023-2024 school year have 1.5 times more anxiety disorders compared to the 2024-2025 school year; students who play games a lot have anxiety disorders 2.15 times higher than normal, and students who stay up late have anxiety disorders 1.87 times higher than normal students; students whose family members have mental illness have 2.21 times higher anxiety disorder in choosing subject combinations than students who do not have family members with mental illness.Conclusions: Anxiety disorder when choosing a subject combination according to the 2018 educational program is a common condition and is related to the year of study, bad habits and family history of mental illness.
Keywords: Anxiety disorders; Zung scale